Geschlechterunterschiede in den Arbeitswerten: eine Analyse für die alten Bundesländer 1980–2000 - Matthias Pollmann-Schult (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2009)
– This research examines changes in job values of women and men from 1980 to 2000 using data from the ALLBUS. Here we address the question of whether gender differences in job values are of particular importance to explain sex segregation in the labour market. Our results suggest that men tend to place a higher value on extrinsic rewards and women attach greater importance to altruistic rewards than men do. However, these gender differences are limited and have narrowed in recent years. In the early 1980s men attached more importance to income and chances of promotion than women did and women indicated a stronger preference to having opportunities to help others, whereas in 2000, we observe gender differences only with regard to altruistic job values. The relatively small gender differences in job values suggest that supply-side explanations for sex segregation - derived from neoclassical and socialisation theory - do not significantly contribute to explain sex segregation in the labour market.
Keywords: 330; Wertorientierung; Wertwandel; Männer; Frauen; Arbeitswelt; Segregation - Determinanten; Westdeutschland; Bundesrepublik Deutschland